How―and Why―Middle School Intensive Reading Teachers Make Adaptations to a Scripted Curriculum. (November 2021) - Chapman, Lindsey A.; Elbaum, Batya
The adoption of highly scripted curricular programs to promote literacy has become increasingly widespread. Little is known, however, about the extent to which teachers implement these programs as prescribed or, instead, make adaptations to the curriculum and its delivery. Even less is known about teachers' reasoning behind this decision-making. Using qualitative thematic analysis, in this study, the authors investigate middle school intensive reading teachers' challenges and solutions to implementing the curricular program mandated by their school district. Analysis of 10 teachers' descriptions of their instructional decision-making highlighted the tensions teachers must navigate to provide effective literacy instruction to students with and without disabilities in a high accountability context. The central construct of negotiation was identified as an explanation of how and why teachers made (or did not make) curricular adaptations.